Deteksi dan Identifikasi Potyvirus pada Ubi Jalar di Tana Toraja, Sulawesi Selatan - Laras Anjarsari; Gede Suastika; Tri Asmira Damayanti (Jurnal Fitopatologi Indonesia, 2013)
Typical viral symptoms including chlorotic and uneven interveinal yellowing on leaves without leaf malformation was observed on sweet potato field in Tana Toraja, South Sulawesi. To identify the causal of the disease, reverse transcription-polymerase chain reaction (RT-PCR) and DNA sequencing were carried out to detect the virus from infected plants. RT-PCR using universal primer for C1 gene of Potyvirus was successfully amplified approximately 683bp DNA fragment. The nucleotide sequences of this C1 gene fragment showed 98% homology to Sweet potato virus G (SPVG). Amplification using specific primer for coat protein (CP) gene of SPVG followed by DNA sequencing confirmed the association of SPVG from infected plants. Further nucleotide analysis shwowed that SPVG isolate from Tana Toraja had 99.2% homology to isolate from Japan. This is the firstt report of SPVG infection on sweet potato in South Sulawesi.